A comparative study on design of static and dynamic cellular manufacturing system under deterministic production environment. (2020) - Ajmal Sheriff F, Mohammed; Jayakumar, V.; Ahmed, Tauseef; Sasi Kumar, P.
Abstract: In job shops and flow line manufacturing plants, the impact of Cellular Manufacturing System (CMS) with recent advancement in Group Technology (GT) and Automated Manufacturing System (AMS) has resulted in minimizing cost involved in machine maintenance and overhead, machine procurement, machine setup and intra/intercell material movement cost. Meanwhile, the industrialist addressed the problem in deciding the planning horizon to design CMS with respect to the change in customer demand pattern. The Classical CMS failed to capture the fickle in part demand and product mix. In the case of Dynamic CMS (DCMS), the fluctuation is considered by dividing the entire planning horizon into smaller periods. In this paper, a real time data of product mix and product demand were collected from an automobile components manufacturing industry located in SIPCOT Industrial Park, Sriperumbudur to visualize the potential benefits of incorporating DCMS. In this work, existing mathematical model has been used for designing DCMS and it is developed further to convert the model as static environment. Evaluation of the obtained CMS design was done by capturing the exact production parameters of the industry and it is found DCMS resulted in promising cell configuration with minimal overall objective value.